Integrating Placebo Effects in General Practice: A Cross-Sectional Survey to Investigate Perspectives From Health Care Professionals in the Netherlands - Smits, Rosanne M.; Veldhuijzen, Dieuwke S.; van Middendorp, Henriët; van der Heijden, Marianne J. E.; van Dijk, Monique; Evers, Andrea W. M. (Frontiers in Psychiatry, 2022)
Objectives: Placebo effects, beneficial treatment outcomes due to non-active treatment components, play an important role in the overall treatment response. To facilitate these beneficial effects it is important to explore the perspectives of health care professionals (HCPs) on the integration of placebo effects in clinical care. Three themes were investigated: knowledge about placebo effects and factors that contribute to these, frequency of placebo use, and attitudes towards acceptability and transparency of placebo use in treatment. Methods: A cross‐sectional survey, according to the Checklist for Reporting Results of Internet E‐Surveys guidelines and STrengthening the Reporting of OBservational Studies in Epidemiology (STROBE), was conducted in the Netherlands in 2020. The survey was conducted in two samples: a (nested) short survey in 78 nurses during working shifts (sample 1) and an extended online survey in 47 general HCPs e.g., medical psychologists, oncologists, surgeons (sample 2). Results: Respondents from both samples reported to be somewhat or quite familiar with placebo effects (24.0% and 47.2% respectively). From the six placebo mechanisms that were presented, mind-body interaction, positive expectations, and brain activity involved in placebo effects were rated as the most influential factors in placebo effects (F(5, 119) = 20.921, p < .001). The use of placebo effects was reported in 53.8% (n = 42) of the nurses (e.g. by inducing positive expectations), and 17.4% of the HCPs (n = 8 reported to make use of pure placebos and 30.4% of impure placebos (n = 14). Attitudes towards placebo use in treatment were acceptant, and transparency was highly valued (both up to 51%). Conclusions: The findings from this study address knowledge gaps in placebo effects in practice and provide insights in attitudes towards the integration of placebo effects from HCPs. Altogether, integrating these findings may potentially optimize treatment outcomes.